Sustainable development policy in Mongolia: National aspirations and local priorities for the resource regions - Davydova, Elena; Tszian, Konstantin (Mongolian Journal of Geography and Geoecology, 2025)
The institutional framework is the most important basis for the functioning of sustainable development instruments. For an intensively developing economy like Mongolia, it is important to maintain harmony between economic, social and environmental concerns. This paper provides an overview of the key features of sustainable development policy in Mongolia. Relevant documentation is reviewed, and the most important priorities are highlighted. Authors have analyzed documents such as Vision for Sustainable Development of Mongolia until 2030 and “VISION 2050”, The Mongolian Green Taxonomy. Sustainable financing instruments are highlighted as the most important aspect of the practical application of the issues under study, especially green loans and social loans, sustainability-related loans. Due to the critical importance of the mining industry for the Mongolian economy, a model territory in the form of Umnugovi aimag is selected, for which the case of the Oyu Tolgoi mine is considered. It is important to note which aspects of policy implementation are left to governmental and non-governmental organizations, and which aspects are taken up by business. Big degree of responsibility regarding ESG-policy currently falls on the private companies. A particular case study of the Oyu Tolgoi revealed how the sustainable development of the resource region is related to the indstrual actor. This particular case study is an example of the successful implementation of such dependence, although it is unlikely to be the case for every private company. Further study of this topic will not only provide concrete analytical reports, but will also contribute to the development of practical solutions to the nature-society nexus in Mongolia.